An Updated View of Cisplatin Transport (Eur. J. Inorg. Chem. 15/2013). Issue 15 (14th May 2013) - Arnesano, Fabio; Losacco, Maurizio; Natile, Giovanni
Abstract : The cover picture shows a model structure of the human copper chaperone Atox1 bound to cisplatin (magenta: Pt; green: Cl; blue: N; white: H; yellow: S) and poses an intriguing question: Is platinum exchanged between transporters as it happens for copper? This major question is still lacking an answer. Details are presented in the Microreview by F. Arnesano, M. Losacco, and G. Natile onp. 2701 ff . For more on the story behind the cover research, see theCover Profile . In the background is "the near‐touching hands", a detail of the Creation of Adam by Michelangelo.